2009
DOI: 10.1021/ja8092373
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Titania Nanosheets with a High Percentage of Exposed (001) Facets and Related Photocatalytic Properties

Abstract: Anatase TiO(2) nanosheets with highly reactive (001) facets exposed have been successfully synthesized by a facile hydrothermal route, taking advantage of a specific stabilization effect of fluorine ion on (001) facets. The percentage of highly reactive (001) facets in such TiO(2) nanosheets is very high (up to 89%). In addition, the as-prepared TiO(2) nanosheets exhibit excellent activity in the photocatalytic degradation of organic contaminants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
1,302
3
14

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,546 publications
(1,387 citation statements)
references
References 23 publications
44
1,302
3
14
Order By: Relevance
“…It is noteworthy that the F-TiO 2 sample has the lowest PL signals among the as-prepared catalysts and P25. It has been reported that the Ti-F group on the F-TiO 2 surface could act as an electrontrapping site to trap the photo-generated electrons, by holding trapped electrons and then transferring them to O 2 adsorbed on the TiO 2 surface [23,34,39]. Thus, the Ti-F group accounts for the very low PL spectra intensity of F-TiO 2 .…”
Section: Uv-vis and Pl Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the F-TiO 2 sample has the lowest PL signals among the as-prepared catalysts and P25. It has been reported that the Ti-F group on the F-TiO 2 surface could act as an electrontrapping site to trap the photo-generated electrons, by holding trapped electrons and then transferring them to O 2 adsorbed on the TiO 2 surface [23,34,39]. Thus, the Ti-F group accounts for the very low PL spectra intensity of F-TiO 2 .…”
Section: Uv-vis and Pl Analysismentioning
confidence: 99%
“…In controllable synthesis of TiO 2 with exposed (0 0 1) facets, fluorine has been commonly used as a morphology-controlling agent to lower the surface energy in order to expose the reactive (0 0 1) facets [23,32,33]. Anatase TiO 2 with a high percentage of the reactive (0 0 1) facets has exhibited excellent photoreactivity, even much better than pure anatase TiO 2 or commercial P25 in photocatalytic reactions, such the oxidation of acetone [23], OH radical generation [24] and the degradation of methylene orange (MO) [34] and methylene blue (MB) [35], etc. However, it is also reported that, compared with the other two facets, (0 0 1) facets are not always more reactive for some reactions, such as the reaction of hydrogen generation under UV light irradiation [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…39 The high-resolution TEM (HRTEM) image (bottom inset in Figure 3b) showed that the lattice fringes spacing of 0.235 nm parallel to the top and bottom facets were assigned to (001) planes of anatase TiO 2 . 46 That is, the composite photocatalysts prepared with 7.2 wt % MWCNTs consisted of MWCNTs wrapping around the anatase TiO 2 spheres with exposed single-crystal {001} facets. The percentage of exposed {001} facets was estimated as 74%.…”
Section: Characterization Of Structure and Morphologymentioning
confidence: 99%
“…Therefore, the CdMoO 4 products with high crystallinity demonstrated excellent photocatalytic activity. On the other hand, the morphologies and exposed facets of photocatalyst are also important to its photocatalytic activity [34][35][36] . Based on the results of this study, the photocatalytic activity of CdMoO 4 is closely related to not only the crystallinity but also the facet.…”
Section: Optical Properties Photocatalytic Activities and Photostabimentioning
confidence: 99%